Ethical Issues Related to Positionality and Reverse Asymmetry in International Development Research: Experiences in Researching South Asian Philanthropy - Kulendrarajah, Nirojan (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2018)
The role of asymmetry and positionality of the researcher-research participant relationship is important for research ethics in international development. However, discourse should take into account instances where 'reverse asymmetry' may exist, and consider developing different strategies and concerns for researchers to consider in this context.